2020
DOI: 10.2147/cmar.s248621
|View full text |Cite
|
Sign up to set email alerts
|

<p>Plasmatic circRNA Predicting the Occurrence of Human Glioblastoma</p>

Abstract: Background: Glioblastoma (GBM) is the most common primary malignant tumor in adult central nervous system and results in disappointing survival outcomes. Although the diagnosis and therapy approach have been developed recently, the prognosis of GBM remains poor. A novel, minimally invasive biomarker for GBM is necessary for early diagnosis or prognosis prediction. Methods: All circRNAs were detected by qRT-PCR in GBM samples including training and validation sets. We used the risk score analysis to assume the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The interest in finding new non-invasive cancer biomarkers for diagnostic, prognostic and response-to-therapy purposes has been increasing in the last few years [45][46][47][48]. This is one of the first studies that focuses on circRNAs as non-invasive diagnostic biomarkers, detectable in GBM patients' liquid biopsies: to the best of our knowledge, only Chen et al published a paper on three plasmatic circRNAs (circFOXO3, circ_0029426, and circ-SHPRH) with a diagnostic value for GBM [49]. Due to their intrinsic resistance to exonucleases and resulting high stability, circRNAs, and especially EV-associated circRNAs, may be considered very good candidate biomarkers [42,45].…”
Section: Discussionmentioning
confidence: 99%
“…The interest in finding new non-invasive cancer biomarkers for diagnostic, prognostic and response-to-therapy purposes has been increasing in the last few years [45][46][47][48]. This is one of the first studies that focuses on circRNAs as non-invasive diagnostic biomarkers, detectable in GBM patients' liquid biopsies: to the best of our knowledge, only Chen et al published a paper on three plasmatic circRNAs (circFOXO3, circ_0029426, and circ-SHPRH) with a diagnostic value for GBM [49]. Due to their intrinsic resistance to exonucleases and resulting high stability, circRNAs, and especially EV-associated circRNAs, may be considered very good candidate biomarkers [42,45].…”
Section: Discussionmentioning
confidence: 99%
“…Risk score analysis revealed that the combination of three circRNAs could distinguish patients with GBM from healthy controls, with an area under the curve value of 0.906. 96 Contrary to the strategy employed by Chen et al, Wang et al evaluated 64 paired glioma tumor tissues and matched adjacent non-tumor tissue samples and found significantly lower circ-SHPRH expression in tumor tissues and cells than in paired non-tumor tissues. 97 The relationship between circ-SHPRH expression and clinical characteristics of glioma was further explored, and the results showed that circ-SHPRH downregulation is strongly associated with larger tumor size and advanced WHO grade.…”
Section: Glioblastomamentioning
confidence: 98%
“…Risk score analysis revealed that the combination of three circRNAs could distinguish patients with GBM from healthy controls, with an area under the curve value of 0.906. 96 …”
Section: Glioblastomamentioning
confidence: 99%
“…They found that miR-138-5p and miR-432-5p jointly targeted nuclear factor of activated T cells 5 and restricted its expression, while circFOXO3 could remove this restriction and promote the proliferation and invasion of GBM cells (Zhang et al, 2019). At the same time, Chen et al (2020) showed that plasma circFOXO3 was highly expressed in patients with GBM and had predictive significance for the occurrence of GBM.…”
Section: Glioblastomamentioning
confidence: 99%
“…Circular RNAs are closely related to the occurrence and development of various human diseases (Aufiero et al, 2019;D'Ambra et al, 2019;Liu et al, 2019;Haque et al, 2020;Li R. et al, 2020). In particular, circRNAs are present in cancer diagnosis, development, drug resistance and circFOXO3 is one of the important ones (Zhang and Xin, 2018;Greene et al, 2019;Chen et al, 2020). The FoxO subfamily of forkhead transcription factors (Fox) widely exists in eukaryotic cells and is involved in the regulation of cell cycle, energy metabolism and tumorigenesis through specific activation of transcription process (Link, 2019).…”
Section: Introductionmentioning
confidence: 99%